ANATOMI DAN IDENTIFIKASI SEPULUH JENIS KAYU DARI KALIMANTAN TIMUR - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1986)
The gross and anatomical features of ten wood species from Marangkayu Forest Area, East Kalimantan, were studied and docribed for identification purposes. Most of the samples observed had characters which matched the previous description of the species or genus. However, one sample, that is Lempung namit (Shorea leprosula Miq. ), showed characters that matched the previous description of the genus only but not the species.